REVITALISASI KETENAGAKERJAAN DAN KESEMPATAN KERJA TERKAIT STRATEGI DAN KEBIJAKAN PEMBANGUNAN PERTANIAN DAN PEDESAAN - ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 3 November 2007)
The fact that a close relationship exist between farmlands and agricultural activities brought about consequence that effort for improving farmers welfare cannot be based only on technological and institutional improvement. The problem to be faced at present a however, that farmlands tend to be increasingly limited, due to competition with other uses of lands, where as people working in the sector of agriculture is steadily, and absolutely increasing, resulting in an increasingly limited average proprietorship and control of land. These reviews discuss the structure of job opportunities and income, and their interrelations, as well as the causal relation between income expenditure levels of the society, in agricultural and non-agricultural sector. Productivity of labor as a production factor is considered for more important in farm role obtaining the income, than labor absorption itself. Agro-ecosystem an ecological disparities should be identified from variables of job opportunities, income, and society expenditure. Economic development induces changes of sectoral economic structure, such from agricultural sector to industrial sector, but isn’t accompanied by labor structural shift. There should be employment also for other sectors, not only for agricultural sectors.
Keywords: Competition, Labor, Farmlands, Farmer’s Income, Job Opportunities.